ANALISIS PENGARUH BUKU CERITA BERGAMBAR BERBASIS DIGITAL TERHADAP KARAKTER SISWA DI SEKOLAH DASAR - Hanisya Nurul Fazrina; Afaf Izzah Kamilah; Intan Lestari Puspasari; Arita Marini (Bajang Institute, 2022)
This study aims to discover how the development of digital storybooks can improve the character of students in elementary schools. One of the places to instill character education in children is at school. Character education can be accomplished during the learning process by adjusting existing subjects. The role of digital storybooks in the formation of the character of elementary school students influences each other. Student-oriented learning must instill that character. In its application, character cultivation wants to be inserted in digital storybooks. The research method used is literature study research. This study uses a qualitative approach. The data collected was obtained, through the process of describing and parsing data from various journals. The variables used in this research are the dependent and the independent variable. The study results show that digital storybooks greatly influence the character formation of elementary school students. Digital storybooks are made by adjusting the material, to be taught by the teacher. Digital storybooks can also adapt to the characters you want to instill in the teaching and learning process.